Evaluating the outcomes of problem-based learning in postgraduate medical education: a systematic review and meta-analysis - Emma A Mensour; Carolyn Tran; Toni Li; Indika Mallawaarachchi; Jennifer Shaw; Sarah Blissett (Canadian Medical Education Journal)
Background: Educators have recently been compelled to incorporate more active instructional formats into medical education, such as problem-based learning (PBL). In view of the mixed outcome data on the use of PBL in postgraduate medical education (PGME), there is a need to synthesize the data to inform the application of PBL in PGME contexts.